Pendampingan dan Pelatihan di Pondok Pesantren dalam Upaya Meningkatkan Kompetensi Terjemah Melalui Pembelajaran Aktif - Makinuddin, Mohammad; Amrulloh, Friendis Syani; Haq, Muhammad A'inul; Alawy, Muhammad (Community: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service project focuses on enhancing translation competence through active learning at Pondok Pesantren Mambaus Sholihin Gresik. The main objective was to improve the translation skills of santri by engaging them in participatory and collaborative learning processes. The research employed a participatory action research (PAR) approach, involving close collaboration between the research team, educators, and santri as active subjects. Activities included interactive translation practice, group discussions, and continuous mentoring to foster better understanding and application of translation techniques. The project successfully increased technical translation skills, motivation, and critical learning attitudes among santri. Furthermore, it led to the emergence of self-managed learning groups and local leaders, indicating a social transformation towards a more independent and adaptive learning culture within the pesantren. This model demonstrates the effectiveness of integrating active learning and community empowerment to achieve sustainable educational improvements in pesantren contexts. Recommendations include institutionalizing active learning methods and strengthening local facilitators to maintain and expand the program’s impact.